Efectividad agronómica y económica de la fertilización líquida en maíz amarillo duro bajo condiciones de secano en el sitio El Limón del cantón Bolívar - Domínguez Morales, Mildred Gissela (2022)
Corn in Ecuador represents an agricultural item of great importance in what corresponds to economic, social and food terms. The objective of this research was to evaluate the agronomic and economic effectiveness of liquid fertilization in hard yellow corn under rainfed conditions. This experiment was developed in the maize zone of Bolivar canton. A randomized complete block design was used with a factorial arrangement of 2x2+2 controls, with four repetitions.The treatments arose fromcombiningtwo genotypes (INIAP H – 601 and INIAP H – 603) and three fertilization techniques (liquid fertilization in drench, liquid injected and granulated). The registered variables were grain yield (RG), agronomic efficiency of N (EAN) and net economic benefit (BEN). The variables RG and EAN were significantly influenced (p<0.05) by the fertilization techniques, regardless of the genotypes that were evaluated. The highest average in RG was obtained with the injected liquid fertilization and in the superficial right with 7136.49 and 6793.04 kg ha-1, correspondingly. Of the same, the liquid fertilization in drench and injected registered the highest average in EAN, with 24.85 and 22.97 kg of grain kg-1 of N applied, correspondingly. In addition, the best BEN were achieved in the injected liquid fertilization and in the drench with 581 and 544 ha-1, correspondingly. Therefore, it is concluded thatapply liquid fertilizer under a rainfed maize planting system in Calceta maize zones to improve the yield and quality of the crop.